First record of the acanthurid fish Zebrasoma xanthurum (Blyth, 1852) in the Mediterranean Sea, with some considerations on the risk associated with aquarium trade - GUIDETTI, P.; MAGNALI, L.; NAVONE, A. (Mediterranean Marine Science, 2015)
The occurrence of a single individual of yellowtail tang Zebrasoma xanthurum (Acanthuridae) from Sardinia island (Italy), probably released from an aquarium, is here reported. This represents the first record of this species in the Mediterranean Sea. The overall information available on Acanthurid fishes and other exotic species in the Mediterranean is discussed in the light of the ongoing ecological changes taking place in rocky reef ecosystems.